Comparison of different methods for isolating CD8+ T lymphocyte‐derived extracellular vesicles and supramolecular attack particles. Issue 3 (13th March 2023) - Jainarayanan, Ashwin K.; Capera, Jesusa; Céspedes, Pablo F.; Conceição, Mariana; Elanchezhian, Mirudula; Thomas, Tom; Bonner, Scott; Valvo, Salvatore; Kurz, Elke; Mahla, Ranjeet Singh; Berridge, Georgina; Hester, Svenja; et al.
Abstract: CD8 + T lymphocytes play vital roles in killing infected or deranged host cells, recruiting innate immune cells, and regulating other aspects of immune responses. Like any other cell, CD8 + T cells also produce extracellular particles. These include extracellular vesicles (EVs) and non‐vesicular extracellular particles (NVEPs). T cell‐derived EVs are proposed to mediate cell‐to‐cell signalling, especially in the context of inflammatory responses, autoimmunity, and infectious diseases. CD8 + T cells also produce supramolecular attack particles (SMAPs), which are in the same size range as EVs and mediate a component of T cell mediated killing. The isolation technique selected will have a profound effect on yield, purity, biochemical properties and function of T cell‐derived particles; making it important to directly compare different approaches. In this study, we compared commonly used techniques (membrane spin filtration, ultracentrifugation, or size exclusion liquid chromatography) to isolate particles from activated human CD8 + T cells and validated our results by single‐particle methods, including nanoparticle tracking analysis, flow cytometry, electron microscopy and super‐resolution microscopy of the purified sample as well as bulk proteomics and lipidomics analyses to evaluate the quality and nature of enriched T cell‐derived particles. Our results show that there is a trade‐off between the yield and the quality of T cell‐derived particles. Furthermore, the protein and lipid composition of the particles is dramatically impacted by the isolation technique applied. We conclude that from the techniques evaluated, size exclusion liquid chromatography offers the highest quality of T cell derived EVs and SMAPs with acceptable yields for compositional and functional studies.